DATABASE The governance of renewable energy auctions: A multidimensional comparative policy analysis - Valenzuela Robles Linares, J; Mathieu, E (University of Oxford, 2024)
Analysis of renewable energy auction practices in Mexico, Morocco and United Kingdom. The accompanying paper is available in the Journal of Comparative Policy Analysis: Research and Practice ( JCPA ).